An uncommon complication of arterial embolization for treatment of epistaxis. Issue 4 (2nd March 2016) - Bobinskas, Alexander M.; Barrett, Michael
Key Clinical Message: Although uncommon, patients should be advised that soft tissue necrosis may be a complication of arterial embolization used for treatment of epistaxis. Abstract : Although uncommon, patients should be advised that soft tissue necrosis may be a complication of arterial embolization used for treatment of epistaxis.